The Sultan Speaks - McJannet, L. author. aut Link
XII, 245 p.
Keywords: The first study of English historical plays about the Turks, using works in Greek, Arabic, and Turkish. Drawing on Bakhtin's concept of the dialogic, McJannet shows that instead of adverse authorial commentary playwrights such as Marlowe and Fulke Greville use dialogue and commentary to enhance the sultan's stature and mitigate his negative acts.